The Satisfaction on Operation of the Sufficiency Household in the Northeast Region - Pontip, Anuwat; Prompakping, Buapun; Phatchaney, Kritsada (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
Housing has been generally conceived as a problem of, or a phenomenon of urban. Recently it housing has become a rural problem. As a result, Community Organization Development Institute (CODI) has extended its Sufficiency Household Project to rural areas. This article derived from a research project on satisfaction of beneficiaries of Rural Sufficiency Household Project of 2561 BE that convers 10 districts of 5 provinces of the Northeast of Thailand. Qualitative methods and tools were employed for data collection, in, including in-depth interview, group discussion, and non-participant observation were. There were attended focus group discussions 2 and project recipients were interviewed. The study found that beneficiaries were satisfied with the three aspects of project activities, these response to needs of beneficiaries, just criteria for recruitment of beneficiaries and the positive impacts of the project on community development. Demand response of beneficial household in the community, requirements and processes of consideration selected beneficial member which should be appropriate and transparent, and positive effect to community in relationships support aspect respectively which are stated and linked together with database systematically. Financial estimate and cooperation of community and other connections which motivate to achieve an achievement and relate to inconveniences of more than 147 beneficial households in the community which be able to efficiently guide other province or region a motivation afterwards.